Management Functions in an Organization PROMAG, Lda-Portus Hibericus - Ferreira, Ana Beatriz; Lopes, Ana Beatriz; Santos, Ana Luisa; Pereira, Adalmiro; Teixeira, Tânia (Archives of Business Research, 2023)
PROMAG has, as its main objective, the production and export of olive oil and various products of Portuguese origin, hence our choice. We wanted to understand and explore how this whole process works, from the raw material to the final product. And then, where management is applied and how all the concepts discussed in the classroom work in practice. In the course of our analysis, we approach different points in the functioning of a company, starting with its birth and what motivated it; we talk a little about its social objective and the story behind the brand, how it all really started and developed. More at a technical level, we addressed the organizational structure – how responsibilities are divided, the leaders we have present; the planning phase and after that planning, the control that has to be applied to all the products that the brand produces and exports. In the final phase of the process, we will talk about how the company is marketed, how the final product is presented to the public and which products are available for sale. In order to be able to carry out a very complete work, we contacted the manager and partner of the company, Rui Pereira, who provided us with all our values ​​and answers to what the work asked of us.